INSTAGRAM AS MEDIUM OF DA’WAH: ANALYZING THE MOTIVES OF SANTRI IN TULUNGAGUNG IN FOLLOWING @ALASANTRI ACCOUNT - Mufti Rasyid; Evi Masitoh (PROGRAM STUDI ILMU KOMUNIKASI, 2023)
Instagram has been growing rapidly in recent years as the most prominent social media platform. Various communities in the world are now familiar with Instagram, including the santri community who study in pesantren (Islamic boarding schools). One of most famous Instagram accounts which makes santri as target audience is @alasantri. This Instagram account has successfully attracted santri in some pesantren in Tulungagung city, East Java. The purpose of this study is to see the use of Instagram as a medium of da’wah by @alasantri account and the motives of santri in Tulungagung in following @alasantri account. This study is using a qualitative descriptive method, using non-participatory observation and interviews for collecting the data. The source of the data are santri of Pondok Pesantren Sirojut Tholibin Tulungagung. The results of this study shows that the strategies used by @alasantri account for da’wah could be classified into academic approach and non-academic approach. Meanwhile, there are some motives of santri in Tulungagung in following @alasantri Instagram account such as cognitive motive, affective motive, personal integrity, personal integration and fantasizing.